Psychological Well-being for Elderly People at Geriatric Centers in Baghdad City - sultan, maythem; aljubory, ali (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To evaluate the levels of Psychological well-being among elderly people and To find out the relationship between socio-demographic characteristics and psychological well-being among elderly people who live in Geriatric centers. Methodology: A descriptive study in which evaluation approach is applied to achieve the objectives of the study the period of the study was from 29 December 2014 to 25 may 2015, The sample is non-probability (purposive sample) of 60 elderly people and selecte according to criteria of sample and for the purpose of the study , ( 40 ) are from Al Rashad and ( 20 ) Sleekh Geriatric centers, A questionnaire which include from 50 items which are distribute across 2 main parts A- The socio-demographic characteristics: ( 8 ) items and B- psychological well-being: ( 42 ) items , Data analysis by using program of SPSS version 20, Descriptive statistical analysis procedures (frequency, percentage, and Statistical table) and inferential statistical analysis procedures (Chi-square test for determine the association between the elderly socio – demographic characteristics and psychological wellbeing ). Results: The results of the study: 58.3% of elderly there age are from 65 to 70 years which is most elderly people in Geriatric centers, The source of income different 51.7% from them is from retirement salary and major causes to been in Geriatric centers 56.7% due to family problem, the high level of psychological wellbeing 21.6% are female , 16.7% of them widowed ,23.3% from them are saying enough in income and there is a significant association between psychological wellbeing and income and source of income. Recommendations: according to the results the study Recommends that Psychological wellbeing is one from most objects that’s studies in advanced world, but in Iraq, there is lack of study about it, so most to increase research about it and work with other organizations, including the media, ministry of health, community organization to improve positive public attitudes towards elderly people and promote a better mental health for them .